Temperature Acclimation Alters the Thermal Tolerance and Intestinal Heat Stress Response in a Tibetan Fish Oxygymnocypris stewarti - Zhu, Tingbing; Li, Xuemei; Wu, Xingbing; Yang, Deguo (Frontiers in Microbiology, 2022)
Numerous studies have shown that thermal tolerance and intestinal heat resistance are strongly associated with temperature acclimation. However, few reports have successfully conducted similar research on fishes from the Qinghai–Tibetan Plateau, an area that is facing the threat of climate warming. Therefore, the present study determined the growth, thermal tolerance, and intestinal heat stress (exposure to 30°C) responses in juveniles of a Tibetan fish, Oxygymnocypris stewarti, acclimated to three temperature levels (10, 15, and 20°C, named as T10, T15, and T20, respectively) for 30 days. The fastest growth was recorded in the T15 group. At 1°C /30 min heating rate, the critical thermal maximum (CTMax) ranged from 31.3 to 32.3°C, and the lethal thermal maximum (LTMax) ranged from 31.8 to 32.6°C among the three acclimation temperatures. According to the results of thermal tolerance tests, the heat stress temperature was set to 30°C. When the water temperature reached 30°C, the expression of the intestinal heat shock protein 70 (HSP70) gene as well as the intestinal microbiome and histology of experimental fish were monitored at 0 h, 2 h, 6 h, and 12 h. The expression of HSP70 reached the highest level at 2 h in all three temperature treatments. The histological analysis showed damage to intestinal cells, including diffuse infiltration of lymphocytes, villi epithelial cell swelling, decrease of intestinal villi length, and cytoplasmic light staining at 2 h in all three temperature treatments. In terms of the intestinal microbiome, phyla Proteobacteria and Firmicutes dominated the treatments at each monitored time in the T10 and T15 groups and at 0 h in T20 group, while phyla Fusobacteria, Proteobacteria, and Cyanobacteria were dominant in treatments at 2 h, 6 h, and 12 h in the T20 group. The overall results indicated that acclimation temperature could affect the growth, thermal tolerance, and intestinal heat stress response of O. stewarti juveniles. As the first report on intestinal heat stress response associated with temperature acclimation in a Tibetan fish, this study will help to understand the potential effects of climate change on highland fishes.